The Role of a Glucosinolate-Derived Nitrile in Plant Immune Responses - Ting, Hieng Ming; Cheah, Boon Huat; Chen, Yu Cheng; Yeh, Pei Min; Cheng, Chiu Ping; Yeo, Freddy Kuok San; Vie, Ane Kjersti; Rohloff, Jens; Winge, Per; Bones, Atle M.; Kissen, Ralph (Frontiers in Plant Science, 2021)
Glucosinolates are defense-related secondary metabolites found in Brassicaceae. WhenBrassicaceae come under attack, glucosinolates are hydrolyzed into different formsof glucosinolate hydrolysis products (GHPs). Among the GHPs, isothiocyanates arethe most comprehensively characterized defensive compounds, whereas the functionalstudy of nitriles, another group of GHP, is still limited. Therefore, this study investigateswhether 3-butenenitrile (3BN), a nitrile, can trigger the signaling pathways involved inthe regulation of defense responses inArabidopsis thalianaagainst biotic stresses.Briefly, the methodology is divided into three stages, (i) evaluate the physiological andbiochemical effects of exogenous 3BN treatment on Arabidopsis, (ii) determine themetabolites involved in 3BN-mediated defense responses in Arabidopsis, and (iii) assesswhether a 3BN treatment can enhance the disease tolerance of Arabidopsis againstnecrotrophic pathogens. As a result, a 2.5 mM 3BN treatment caused lesion formationin Arabidopsis Columbia (Col-0) plants, a process found to be modulated by nitric oxide(NO). Metabolite profiling revealed an increased production of soluble sugars, Krebscycle associated carboxylic acids and amino acids in Arabidopsis upon a 2.5 mM 3BNtreatment, presumably via NO action. Primary metabolites such as sugars and aminoacids are known to be crucial components in modulating plant defense responses.Furthermore, exposure to 2.0 mM 3BN treatment began to increase the production ofsalicylic acid (SA) and jasmonic acid (JA) phytohormones in Arabidopsis Col-0 plants inthe absence of lesion formation. The production of SA and JA in nitrate reductase loss-offunction mutant (nia1nia2) plants was also induced by the 3BN treatments, with a greaterinduction for JA. The SA concentration innia1nia2plants was lower than in Col-0 plants,confirming the previously reported role of NO in controlling SA production in Arabidopsis.A 2.0 mM 3BN treatment prior to pathogen assays effectively alleviated the leaf lesionsymptom of Arabidopsis Col-0 plants caused byPectobacterium carotovorumssp.carotovorumandBotrytis cinereaand reduced the pathogen growth on leaves. Thefindings of this study demonstrate that 3BN can elicit defense response pathwaysin Arabidopsis, which potentially involves a coordinated crosstalk between NO andphytohormone signaling.